2017
DOI: 10.1007/s00586-017-5324-z
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral stress and age may contribute to increased pelvic incidence: an analysis of 1625 adults

Abstract: PI is higher in female patients and in older patients, especially those over 45 years old. Spinal malalignment also may have a role in increased PI due to increased L5-S1 bending moment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Our results were similar to those in previous studies [6, 24]. However, several studies reported that PI was influenced by age and significantly larger in late adulthood [25, 26]. The differences between our study and these studies are unclear.…”
Section: Discussionsupporting
confidence: 88%
“…Our results were similar to those in previous studies [6, 24]. However, several studies reported that PI was influenced by age and significantly larger in late adulthood [25, 26]. The differences between our study and these studies are unclear.…”
Section: Discussionsupporting
confidence: 88%
“…A small pelvic incidence angle corresponds to a narrow pelvis (small anteroposterior dimension), while a large angle indicates a broad one (large anteroposterior dimension). In elderly over 75 years old, or some specific long fusion constructs, ligament loosening can produce some degrees of variations [6][7][8].…”
Section: Definition Of the Pelvic Parameters (Fig 3a-c)mentioning
confidence: 99%
“… 17 Nevertheless, some changes can be found due to sacroiliac joint movement (nutation and contra-nutation) caused by ageing or surgical lumbar fusion, usually not exceeding 5°. 18 , 19 PI is closely considered a fixed parameter, characteristic of each patient’s individuality, and clinically determines spino-pelvic interactions. 20 Furthermore, LL angle ( Fig.…”
Section: Spino-pelvic Interactionsmentioning
confidence: 99%